A New Inner Surface Attrition Treatment for Strengthening Metallic Tubular Structures. Issue 3 (15th January 2019) - Li, Ying; Wu, Ge; Liu, Long; Lu, Jian
Abstract : Based on analytical modeling and simulation aided calculations, a systematic assessment of the surface mechanical attrition treatment (SMAT) on the inner surface of a metallic tubular structure, is presented in this work for the first time. With the help of extensive statistical analysis and dynamic simulations, an optimal design of the key SMAT components is theoretically derived for the best inner surface attrition effect, which is thereafter used for the quasi‐static uniaxial compression tests. A remarkable strengthening effect from the inner surface treatment is observed, which can be attributed to the formation of nano‐twins and nano ϵ‐martensite structures due to the severe pre‐processed strain. Interestingly, no α'‐martensite is observed through transmission electron microscope (TEM). This work provides a framework for the optimal design of attrition treatment for complex surfaces, which can thus greatly extend the application of SMAT technology. Abstract : A new method to apply surface attrition treatment on the inner wall of tubular structures is presented. By taking advantages of analytical modeling and simulation‐aided calculations, the optimal treatment can be designed and achieved. This new treating method helps increase the strength of stainless steel tubes.